SARS-CoV-2 spike-specific regulatory T cells (Treg) expand and develop memory in vaccine recipients suggesting a role for immune regulation in preventing severe symptoms in COVID-19 - Franco, Alessandra; Song, Jaeyoon; Chambers, Christina; Sette, Alessandro; Grifoni, Alba (Autoimmunity (Chur, Switzerland), 2023)
We enrolled healthy subjects that received 2 to 4 injections of mRNA-based vaccination to prevent COVID-19 months to a year from the last vaccine boost, and we found numerous SARS-CoV-2 spike-specific regulatory T cell (Treg) that developed T cell memory as effector memory T cells (T ) and central memory T cells (T ). CD4+ CD25 Treg expressed the chemokine receptor CCR6 in a considerable percentage, suggesting T cell homing to the vascular endothelium, lung and gut epithelial cells and brain. Treg phenotype was different than peripherally-induced Treg (pTreg) that revert from pro-inflammatory T cells under repeated stimulatory conditions, suggesting that SARS-CoV-2 spike-specific Treg differentiated from naïve T cells in tissues where the SARS-CoV-2 spike proteins were synthetized. Twenty two of 22 subjects studied responded to vaccination developing a spike-specific CD4+ T helper (Th)1 response, and 20 of 22 developing a spike-specific CD8+ cytotoxic T cells (CTL) response. However, in vaccine recipients the expansion of spike-specific pro-inflammatory T cells was less significant than the expansion of spike-specific Treg. Effector (T ) and central memory (T ) Treg were numerous as early as after two vaccine doses, with no significant differences following additional vaccine boosts. In co-culture experiments under stimulatory conditions, Treg regulated naïve T cell differentiation toward a pro-inflammatory phenotype and suppressed interferon (IFN)γ production by SARS-CoV-2-specific CD4 + Th1 cells.